POTENSI AIR KELAPA DALAM PROSES FERMENTASI BIOETANOL DENGAN PENAMBAHAN NPK DAN TWEEN80TM - Turnip, Titus T; Restuhadi, Fajar '; Rossi, Evy ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study was conducted to determine the optimization of production of bioethanol with a combination of coconut water, tween80 and NPK as nutrient Saccharomyces cerevisiae to produce ethanol using a fermentation technique Very High Gravity Fermentation. This research was conducted experiments with four treatments and measurement in duplicate. Combination of NPK levels are U1 (0.2%), U2 (0.4%), U3 (0.6%) and U4 (0.8%). Observations were made every 24 hours; covering sugar, ethanol content, the number of cells, and pH. Data were analyzed descriptively by using a tabular or graphical. The best treatment is a combination of U4 (NPK 0.8%) which resulted in the largest ethanol 11%. Keywords:Coconut water, tween80, NPK, Bioethanol, Very High Gravity Fermentation